2008
DOI: 10.1007/s00128-008-9462-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Concentrations of Ethinylestradiol, 17β-Estradiol, and Medroxyprogesterone have Little Effect on Reproduction and Survival of Ceriodaphnia dubia

Abstract: Wastewater effluent contains synthetic and natural hormones, often in complex mixtures, that may be associated with reproductive abnormalities in fish and other aquatic biota. We exposed the sentinel invertebrate Ceriodaphnia dubia to the natural estrogen 17beta-estradiol (E(2)), a synthetic estrogen, ethinylestradiol (EE(2)), and a synthetic progestin, medroxyprogesterone in a 7-day test. These compounds had no significant effect on reproduction or survival even at 10(6) times the concentrations at which repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Concerning invertebrates such as the amphipod Hyalella azteca it was observed that at sub-lethal concentrations of EE2 (0.1-10 µg L −1 ) sexual development of males was affected [158]. On the other hand, the estrogens E2 and EE2 did not show significant effects on reproduction or survival of C. dubia even at concentrations of 1 and 0.5 mg L −1 , respectively [159]. According to many authors, the concentrations of estrogens detected in the environment may not post a threat to humans.…”
Section: Sex Hormonesmentioning
confidence: 98%
“…Concerning invertebrates such as the amphipod Hyalella azteca it was observed that at sub-lethal concentrations of EE2 (0.1-10 µg L −1 ) sexual development of males was affected [158]. On the other hand, the estrogens E2 and EE2 did not show significant effects on reproduction or survival of C. dubia even at concentrations of 1 and 0.5 mg L −1 , respectively [159]. According to many authors, the concentrations of estrogens detected in the environment may not post a threat to humans.…”
Section: Sex Hormonesmentioning
confidence: 98%
“…However, the LC 50 values obtained in the acute mortality tests on fish are in the range of mg L −1 [10]. In contrast to fish, no receptors for EE2 have been found in crustaceans, in which the observed effects of EE2 are minor [11], [12]. Compared to vertebrates, invertebrates have fewer identified orthologs to human drug targets.…”
Section: Introductionmentioning
confidence: 96%
“…For example, although the estrogen receptor (ER) is well conserved across vertebrate species (Baker 2011), a functional ortholog has not been found in invertebrate species (Baker et al 2008; Thomson et al 2009). Therefore, chemicals that bind to the ER should affect vertebrates more than invertebrates, regardless of dose—a prediction confirmed in comparative studies (Goto and Hiromi 2003; Jukosky et al 2008; Santos et al 2007). …”
Section: Use Of Alternative Species and In Vitro Assays In An Aop Framentioning
confidence: 63%